2013
DOI: 10.4236/ijcns.2013.63017
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence Based Model for Channel Status Prediction: A New Spectrum Sensing Technique for Cognitive Radio

Abstract: The recent phenomena of tremendous growth in wireless communication application urge increasing need of radio spectrum, albeit it being a precious but natural resource. The recent technology under development to overview the situation is the concept of Cognitive Radio (CR). Recently the Artificial Intelligence (AI) tools are being considered for the topic. AI is the core of the cognitive engine that examines the external and internal environment parameters that leads to some postulations for QoS improvement. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…From Figure 2, it is generally observed that the scientific literature bases the representation of the activity of the primary users with methodologies that have an important computational cost such as [13], [14], [15], [16] among others, being unviable in applications of open field when the conservation of energy is important [11]. An alternative, which could solve these shortcomings by increasing efficiency, are models based on self-learning that provide feedback from their own mistakes to enhance future performance, as is the case with RNNs.…”
Section: Scientific Reviewmentioning
confidence: 99%
“…From Figure 2, it is generally observed that the scientific literature bases the representation of the activity of the primary users with methodologies that have an important computational cost such as [13], [14], [15], [16] among others, being unviable in applications of open field when the conservation of energy is important [11]. An alternative, which could solve these shortcomings by increasing efficiency, are models based on self-learning that provide feedback from their own mistakes to enhance future performance, as is the case with RNNs.…”
Section: Scientific Reviewmentioning
confidence: 99%
“…Therefore, this structure may also be used further for the prediction of the output in such types of environments. An ANN has also been used for making the CR to be able to learn from that of the environment and take a decision (Pattanayak et al, 2013).…”
Section: Introductionmentioning
confidence: 99%